Effects of changes in rock microstructures on permeability: 3‐D printing investigation - D. Head; T. Vanorio (Geophysical Research Letters)
Abstract Rocks are naturally heterogeneous; two rock samples with identical bulk properties can vary widely in microstructure. Understanding how the microstructure and bulk properties of rocks then evolve during experiments and computations simulating diagenesis is inherently a multiscale problem. The advent of modern 3‐D printing has provided an unprecedented opportunity to link those scales by combining the strengths of digital and experimental rock physics. In this study, we take a computerized tomography‐scanned model of a natural carbonate pore space then iteratively digitally manipulate, 3‐D print, and measure the flow properties in the laboratory. This approach allows us to access multiple scales digitally and experimentally and test hypotheses about how changes in rock microstructure due to compaction and dissolution affect bulk transport properties in a repeatable manner.